Pengaruh Kualitas Terhadap Loyalitas Melalui Kepuasan Konsumen PT. Phapros, Tbk. - Abdul Hamid Suryo Negoro (Jurnal Ekonomi dan Manajemen, 2019)
The purpose of this study is 1) To determine product quality, service quality, customer satisfaction and loyalty 2) analyze product quality influences satisfaction 3) analyze service quality influences satisfaction 4) analyze product quality has an effect on loyalty 5) analyze influential service quality to loyalty 6) To analyze satisfaction influences loyalty 7) To analyze product quality has an effect on loyalty through satisfaction 8) To analyze service quality has an effect on loyalty through satisfaction. The data analysis technique used in this study is path analysis. Conclusion: 1) Product quality is included in the good category, good service quality, satisfied satisfaction and product loyalty in the high category. 2) Product quality has an effect on consumer satisfaction. 3) Quality of service has an effect on customer satisfaction, 4) Product quality has an effect on consumer loyalty. 5) Quality of service has an effect on consumer loyalty, 5) Satisfaction influences consumer loyalty 6) Product quality influences loyalty through satisfaction.7) Quality of service influences loyalty through satisfaction.